Phase change fiber membrane with composite core-sheath structure as well as preparation method and application of phase change fiber membrane
By uniformly dispersing hydroxylated boron nitride in the sheath layer of the phase change fiber membrane, and using core sheath structure and ultrasonic dip coating and cold pressing treatment, the problems of low thermal conductivity and easy leakage of existing phase change materials are solved. A composite phase change fiber membrane with high latent heat and high thermal conductivity is realized, suitable for thermal management of electronic devices and wearable devices.
Patent Information
- Application Number
- CN202411744022.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-02-11
Smart Images

Figure CN119411317A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of development of functionalized phase-change fiber materials, and relates to a phase-change fiber membrane with a composite core-sheath structure, and a preparation method and application thereof. Background Art
[0002] With the continuous development of science and technology, electronic devices and wearable devices are developing towards miniaturization and high integration. The heat dissipation problem of devices faces huge challenges. Overheating caused by heat accumulation will greatly reduce the operating efficiency, reliability and life of these devices and equipment, and even cause fire risks. In addition, overcooling of equipment at night or in extreme environments will also lead to poor operation. In recent years, intelligent thermal regulation technology has received great attention, and thermal energy storage technology (TES) has become one of the most promising energy storage technologies. Among them, latent heat storage (LHS) technology based on phase change material (PCM) has attracted widespread attention due to its higher energy storage density and better stability and controllability in a small temperature range, and is considered to be the most promising thermal energy storage technology. Phase change materials can reversibly absorb and release huge thermal energy during melting and crystallization. Combining them with electronic devices and wearable devices can absorb the heat generated during the operation of the device and release the stored heat when needed, providing a suitable operating temperature for electronic devices or wearable devices. The current phase change component is mainly polyethylene glycol, and the phase change point of polyethylene glycol is usually between 5 and 20 ° C, which makes it have good heat storage and release capabilities within a specific temperature range. At the same time, polyethylene glycol has a high phase change latent heat and can absorb and release a large amount of heat energy. However, the thermal conductivity of polyethylene glycol is relatively low, which limits the efficiency of its heat transfer. In addition, since polyethylene glycol has fluidity in a molten state, it is easy to leak out of the packaging material, which limits its application in equipment that requires long-term stable operation. The existing technology has developed composite materials to improve the thermal performance of polyethylene glycol, but there is a problem of limited latent heat retention, that is, the composite material cannot completely retain the phase change latent heat performance of polyethylene glycol. At the same time, when pursuing high thermal conductivity or anti-leakage performance, the flexibility of the material is reduced, which limits its application in devices that need to be bent, folded or worn. Summary of the invention
[0003] In response to the problems existing in the prior art, the present invention provides a phase change fiber membrane with a composite core-sheath structure and a preparation method and application thereof, thereby solving the technical problems in the prior art that the phase change material has low thermal conductivity and is easy to leak, while the composite phase change material has limited latent heat retention and poor flexibility.
[0004] The present invention is achieved through the following technical solutions: A method for preparing a phase change fiber membrane with a composite core-sheath structure comprises the following steps: S1: dissolving polyacrylonitrile in N'N-dimethylformamide, stirring to completely dissolve it, adding hydroxylated boron nitride, and ultrasonically treating to uniformly disperse the hydroxylated boron nitride to obtain a sheath spinning precursor solution; dissolving polyethylene glycol in N'N-dimethylformamide, stirring to melt it, and using it as a core spinning precursor solution; S2: preparing a phase change fiber membrane with a core-sheath structure by a coaxial electrospinning process using the sheath spinning precursor solution and the core spinning precursor solution; S3: placing the phase change fiber membrane with the core-sheath structure in an ethanol dispersion of hydroxylated boron nitride, ultrasonically dip-coating the membrane, and then cold-pressing the membrane to obtain the phase change fiber membrane with the composite core-sheath structure.
[0005] Preferably, in step S1, the mass / volume concentration of polyacrylonitrile in the sheath spinning precursor solution is 10% to 12%, and the added amount of hydroxylated boron nitride is not more than 5%.
[0006] Preferably, in step S1, the mass / volume concentration of polyethylene glycol in the core layer spinning precursor solution is 50% to 70%.
[0007] Preferably, in step S1, the molecular weight of the polyethylene glycol is 800-6000.
[0008] Preferably, in step S2, during the coaxial electrospinning process, a stainless steel coaxial needle is used, the outer needle of the stainless steel coaxial needle is (15~17)G, and the inner needle is (20~22)G; the pumping flow rate of the sheath spinning precursor solution is 1.2~1.5 mL / h, the pumping flow rate of the core spinning precursor solution is 0.24~0.72mL / h, the applied voltage is 20~25kV, the spinning distance is 12~17 cm, and the roller speed is 100~120 rpm.
[0009] Preferably, in step S3, the concentration of the ethanol dispersion of hydroxylated boron nitride is 1-1.5 mg / mL.
[0010] Preferably, in step S3, the ultrasonic dip coating time is 30 to 70 min, and the cold pressing treatment is performed at room temperature after vacuum drying. The pressure of the cold pressing treatment is 10 to 15 MPa, and the time is 20 to 30 min.
[0011] A phase change fiber membrane with a composite core-sheath structure is prepared by the above preparation method.
[0012] The above-mentioned phase change fiber membrane with a composite core-sheath structure has a melting enthalpy of 71.38~114.29 J / g, an in-plane thermal conductivity of 0.10~0.21 W / (m·K), and an out-of-plane thermal conductivity of 1.23~2.45 W / (m·K).
[0013] Application of the above-mentioned phase change fiber membrane with composite core-sheath structure in electronic devices or wearable devices.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a phase change fiber membrane with a composite core-sheath structure. In the method, hydroxylated boron nitride is added to a sheath spinning precursor solution, and is evenly dispersed by ultrasonic treatment, so as to ensure that h-BN particles with high thermal conductivity are evenly distributed in the sheath layer of the fiber. When the sheath layer containing h-BN is combined with a phase change fiber membrane with polyethylene glycol (PEG) as a core layer, the high thermal conductivity of h-BN can effectively transfer heat from the outside of the fiber to the internal phase change material (PEG), thereby improving the thermal conductivity of the entire fiber membrane. The design of the core-sheath structure enables heat to be efficiently transferred along the axial direction of the fiber, further enhancing the thermal conductivity of the fiber membrane. In addition, the design of the core-sheath structure enables the phase change material (PEG) to be wrapped inside the sheath layer, forming a relatively closed space. This structure can effectively prevent the phase change material from leaking when subjected to external pressure or temperature changes. The sheath material (a mixture of polyacrylonitrile and h-BN) has high mechanical strength and stability, and can protect the internal phase change material from being affected by the external environment. Finally, the fiber membrane is placed in an ethanol dispersion of h-BN for ultrasonic dip coating and cold pressing, which can further enhance the thermal conductivity, compactness and mechanical strength of the sheath layer, and further reduce the risk of leakage of the phase change material. At the same time, the method prepares the phase change fiber membrane by coaxial electrospinning, effectively ensuring the flexibility of the phase change fiber membrane. The composite core-sheath structure phase change fiber membrane obtained by the present invention has good high latent heat and high thermal conductivity. This composite core-sheath structure phase change fiber membrane not only improves the thermal conductivity of the fiber membrane by introducing high thermal conductivity hydroxylated boron nitride and adopting the design of the core-sheath structure, but also effectively prevents the leakage of the phase change material, and combines coaxial electrospinning to ensure the flexibility of the composite fiber membrane, which has significant beneficial effects, and can be used in electronic devices or wearable devices to buffer ambient temperature fluctuations and maintain a safe and comfortable temperature for a long time.
[0015] Furthermore, in step S1, the mass / volume concentration of polyacrylonitrile in the sheath spinning precursor solution is 10% to 12%, which can effectively ensure the fluidity of the solution while ensuring that the fiber has good strength and toughness. The PAN solution within this concentration range is easy to form a continuous fiber structure during the spinning process, and the diameter and morphology of the fiber are well controllable. The addition amount of hydroxylated boron nitride is not more than 4%, which can ensure that the sheath layer has good flexibility and mechanical strength while maintaining high thermal conductivity. Too much h-BN may cause the sheath layer to become brittle and hard, affecting the overall performance of the fiber. This parameter can not only ensure the fiber-forming property and mechanical strength of the fiber, but also significantly improve the thermal conductivity of the fiber.
[0016] Further, in step S1, the mass / volume concentration of polyethylene glycol in the core layer spinning precursor solution is 50%~70%, which can ensure that the content of PEG in the core layer is high enough, thereby maximizing the retention of the phase change latent heat of PEG, so that the core layer can absorb and release more heat, and provide more effective thermal management for electronic devices or wearable devices. At the same time, within this concentration range, PEG can form a solution with a certain fluidity, which is conducive to the preparation of a uniform fiber structure through a coaxial electrospinning process. At the same time, the PEG solution also exhibits good fiber-forming properties at this concentration, which can ensure that the fiber is not broken or blocked during the preparation process, and ensure the continuity and consistency of the fiber. That is, setting the mass / volume concentration of polyethylene glycol to 50%~70% as the core layer spinning precursor solution can ensure that the prepared phase change fiber membrane has excellent thermal management performance, good fluidity and fiber-forming properties, as well as adjustable core layer thickness and heat capacity.
[0017] Further, in step S1, the molecular weight of the polyethylene glycol is 800-6000, and the PEG of this molecular weight has a higher phase change latent heat and can store and release more heat. At the same time, using PEG with a molecular weight in the range of 800-6000 as the main component of the core layer spinning precursor solution can ensure that the fiber has stable performance during the preparation process. PEG in this molecular weight range usually has good solubility and spinnability, and can form a uniform and continuous fiber structure. In addition, the distribution of PEG of this molecular weight in the fiber is also relatively uniform, which is conducive to improving the overall performance of the fiber. At the same time, within this molecular weight range, the price of PEG is relatively moderate, which can reduce the material cost of the phase change fiber membrane. This is of great significance for large-scale production and commercial applications, and helps to promote the application of phase change fiber membranes in the field of thermal management of electronic devices and wearable devices. Therefore, selecting polyethylene glycol with a molecular weight of 800-6000 as the main component of the core layer spinning precursor solution can achieve precise control of the phase change temperature, optimize the phase change latent heat, improve the stability and thermal stability of fiber performance, and reduce material costs.
[0018] Furthermore, in step S2, a stainless steel coaxial needle is used in the coaxial electrospinning process, wherein the outer needle of the stainless steel coaxial needle is (15~17)G and the inner needle is (20~22)G; the pumping flow rate of the sheath spinning precursor solution is 1.2~1.5 mL / h, the feeding rate of the core spinning precursor solution is 0.24~0.72mL / h, the applied voltage is 20~25kV, the spinning distance is 12~17 cm, and the roller speed is 100~120 rpm, wherein the use of the stainless steel coaxial needle ensures that the needle has sufficient strength and precision and can stably produce continuous fibers; the pumping flow rate of the sheath spinning precursor solution is set to 1.2~1.5 mL / h, and this flow rate range ensures the uniformity and stability of the sheath solution, which helps to form a continuous sheath structure. At the same time, the appropriate flow rate is also conducive to controlling the diameter and morphology of the fiber; the feed rate of the core layer spinning precursor solution is 0.24~0.72 mL / h, and this rate range ensures that the core layer solution can stably flow into the coaxial needle and form a uniform core-sheath structure with the sheath layer solution. At the same time, by adjusting the feed rate, the content and distribution of the core layer in the fiber can be controlled; the applied voltage is 20~25 kV, and this voltage range provides sufficient electric field force to accelerate the spinning droplets in the electric field and stretch them into fibers. Higher voltage helps to form finer fibers, but too high voltage may cause corona discharge and affect the quality of the fiber; the spinning distance is set to 12~17 cm, and this distance range ensures that the spinning droplets have enough flight time in the electric field to fully stretch and solidify. At the same time, the appropriate spinning distance is also conducive to controlling the diameter and morphology of the fiber. The roller speed is 100~120 rpm, and this speed range helps to collect the fibers and control the arrangement and orientation of the fibers. The appropriate speed can ensure that the fibers are evenly distributed on the roller to form a dense fiber membrane.
[0019] Furthermore, in step S3, the concentration of the ethanol dispersion of hydroxylated boron nitride is 1-1.5 mg / mL, which is conducive to forming a stable dispersion. In this concentration range, the h-BN particles have good dispersibility in ethanol and are not prone to agglomeration or precipitation. Dispersing h-BN in ethanol can be easily mixed with the sheath spinning precursor solution to improve the compatibility of h-BN with the polymer, thereby enhancing the mechanical properties and thermal stability of the composite fiber. By selecting a dispersion concentration of 1-1.5 mg / mL, the content of h-BN in the composite fiber can be accurately controlled. This concentration range ensures that the amount of h-BN added is sufficient to enhance the thermal conductivity of the composite fiber, and avoids the increase in fiber brittleness and the decrease in mechanical properties caused by excessive h-BN content.
[0020] Further, in step S3, the ultrasonic dipping time is 30 to 70 min, and the cold pressing treatment is performed at room temperature after vacuum drying. The pressure of the cold pressing treatment is 10 to 15 MPa, and the time is 20 to 30 min. The ultrasonic dipping time is set to 30 to 70 min, which ensures that the hydroxylated boron nitride (h-BN) in the sheath spinning precursor solution can be evenly and fully dispersed on the surface or inside of the fiber. The effect of ultrasound can promote the dispersion of h-BN particles in the solution and reduce agglomeration, thereby improving the uniformity of h-BN dispersion in the fiber. A longer dipping time helps to fully contact and bond h-BN with the fiber and enhance the thermal conductivity of the fiber. The vacuum drying process can effectively remove the residual moisture and solvent in the fiber and ensure the dryness and quality of the fiber. The fiber structure after drying is more stable, which is conducive to maintaining the shape and performance during the subsequent cold pressing treatment. Cold pressing treatment at room temperature avoids the potential impact of high temperature on fiber performance and ensures the integrity of the fiber structure and performance stability. The cold pressing pressure is set to 10-15 MPa and the time is 20-30 min. This parameter range can ensure the close bonding between the fibers and prevent the fibers from being damaged due to excessive pressure. Through the cold pressing treatment, the gaps between the fibers are compressed, which improves the density and overall performance of the fibers. The cold pressing treatment also helps to improve the thermal conductivity of the fibers because the tight fiber structure is conducive to heat transfer. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 It is a schematic diagram of the process of preparing a phase change fiber membrane with a composite core-sheath structure in the present invention; Figure 2 The SEM images of the phase change fiber membrane with a composite core-sheath structure prepared in Example 1 of the present invention, wherein (a) is before cold pressing, and (b) is after cold pressing; Figure 3 The infrared spectrum of the phase change fiber membrane with a composite core-sheath structure prepared by BNNS and Example 1 of the present invention; Figure 4 The DSC graph of the phase change fiber membrane with a composite core-sheath structure prepared in Example 1 of the present invention, wherein: (a) a thermal cycle DSC curve; (b) the melting / crystallization temperature and melting / crystallization enthalpy of the 1st, 50th, 100th, 150th and 200th thermal cycles; Figure 5The in-plane and out-of-plane thermal conductivity bar graphs of the phase change fiber membrane with a composite core-sheath structure obtained in Example 1 of the present invention; Figure 6 This is a shape stability test diagram of the phase change fiber membrane with a composite core-sheath structure prepared in Example 1 of the present invention; Figure 7 The SEM images and TEM images of the PAN@PEG membranes prepared in Examples 4 to 8 of the present invention, wherein (a) and (e) are the SEM image and TEM image of Example 4, respectively; (b) and (f) are the SEM image and TEM image of Example 5, respectively; (c) and (g) are the SEM image and TEM image of Example 6, respectively; (d) and (h) are the SEM image and TEM image of Example 7, respectively; PAN@PEG5 is the SEM image of the sample prepared in Example 8; Figure 8 The SEM images and TEM images of the BPAN@PEG membranes prepared in Examples 1 and 9-11 of the present invention, wherein (a)-(d) are SEM images of the samples prepared in Example 1 and Examples 9-11, respectively, and (e) is a TEM image of the sample prepared in Example 1. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0025] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0026] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0027] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0028] like Figure 1 As shown, the present invention provides a method for preparing a phase change fiber membrane with a composite core-sheath structure, comprising the following steps: S1: dissolving polyacrylonitrile in N'N-dimethylformamide, stirring to completely dissolve it, adding hydroxylated boron nitride, and ultrasonically treating to uniformly disperse the hydroxylated boron nitride to obtain a sheath spinning precursor solution; dissolving polyethylene glycol in N'N-dimethylformamide, stirring to melt it, and using it as a core spinning precursor solution; The mass / volume concentration of polyacrylonitrile in the sheath spinning precursor solution is 10% to 12%, that is, the concentration of polyacrylonitrile in the sheath spinning precursor solution is 10% to 12% (W / V), and the amount of hydroxylated boron nitride added is not more than 5%, which means that the amount of hydroxylated boron nitride added is not more than 5 wt% of the mass percentage of polyacrylonitrile, and preferably, the amount of hydroxylated boron nitride added is not more than 4%. The mass / volume concentration of polyethylene glycol in the core spinning precursor solution is 50% to 70%. The molecular weight of the polyethylene glycol is 800 to 6000.
[0029] S2: preparing a phase change fiber membrane with a core-sheath structure by a coaxial electrospinning process using the sheath spinning precursor solution and the core spinning precursor solution; In the coaxial electrospinning process, a stainless steel coaxial needle is used, the outer needle of the stainless steel coaxial needle is (15~17)G, the inner needle is (20~22)G, the pumping flow rate of the sheath spinning precursor solution is 1.2~1.5 mL / h, the feed rate of the core spinning precursor solution, that is, the pumping flow rate is 0.24~0.72mL / h, the applied voltage is 20~25 kV, the spinning distance is 12~17 cm, and the roller speed is 100~120 rpm.
[0030] S3: placing the phase change fiber membrane with the core-sheath structure in an ethanol dispersion of hydroxylated boron nitride, ultrasonically dip-coating the membrane, and then cold-pressing the membrane to obtain the phase change fiber membrane with the composite core-sheath structure.
[0031] The concentration of the ethanol dispersion of hydroxylated boron nitride is 1-1.5 mg / mL. The ultrasonic dip coating time is 30-70 min. After vacuum drying, the cold pressing treatment is performed at room temperature. The pressure of the cold pressing treatment is 10-15 MPa and the time is 20-30 min.
[0032] In addition, the present invention also discloses a phase change fiber membrane with a composite core-sheath structure prepared by the above method, wherein the phase change fiber membrane with a composite core-sheath structure has a melting enthalpy of 71.38 J / ~114.29, an in-plane thermal conductivity of 0.100~0.210 W / (m·K), and an out-of-plane thermal conductivity of 1.232~2.450 W / (m·K).
[0033] Furthermore, the invention discloses the application of the phase change fiber membrane with the composite core-sheath structure in electronic devices or wearable devices.
[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0035] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0036] Example 1 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40 °C for 4 h. 4 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring it at 60 °C for 4 h as the core spinning precursor solution.
[0037] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as BPAN@PEG4.
[0038] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on BPAN@PEG4 by combining ultrasonic dip coating and cold pressing. Specifically, h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL, and a uniformly dispersed h-BNNS dispersion was obtained after 2 h of water bath ultrasound and 12 h of mechanical stirring. The BPAN@PEG4 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed under vacuum drying at room temperature for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer, denoted as BPAN@PEG / BNNS. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure, i.e., a phase change fiber membrane with a composite core-sheath structure, denoted as BPAN@PEG / BNNS-p.
[0039] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 113.05 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.450 W / (m·K) and 0.210 W / (m·K), respectively.
[0040] The h-BNNS in the present invention is prepared by boric acid (BA)-assisted ball milling. Specifically, 1 g of h-BN powder is fully mixed with 4 g of BA, and then placed in a vertical planetary ball mill and operated at 500 rpm for 24 h at room temperature. The ball-milled product is dispersed in deionized water, and the dispersion is centrifuged at 3000 rpm for 15 min, and the supernatant is retained to remove large pieces of unpeeled h-BN. The supernatant is further centrifuged at 8000 rpm for 15 min, and the lower precipitate is retained. Finally, the mixture is dried in a vacuum oven at 60 o C for 24 h to obtain h-BNNS.
[0041] In order to observe the microstructure of the phase change fiber membrane with a composite core-sheath structure prepared by the technical solution of the present invention, BPAN@PEG / BNNS and BPAN@PEG / BNNS-p prepared in this embodiment were taken as examples to perform SEM characterization tests. The test results are shown in FIG. Figure 2 As shown, Figure 2 (a) is the SEM image of BPAN@PEG / BNNS. Figure 2(b) is the SEM image of BPAN@PEG / BNNS-p. The results show that h-BNNS with appropriate concentration can evenly cover the composite fiber by ultrasonic-assisted dip coating for 50 min. After cold pressing, h-BNNS is densely attached to the fiber to form a continuous thermal conductive network without destroying the core-sheath structure of the coaxial fiber. The h-BNNS thermal conductive network in BPAN@PEG4 / BNNS-p consists of two parts, one is the h-BNNS in the sheath solution, and the other is the h-BNNS dip-coated by ultrasonic coating, which gives it high thermal conductivity without damaging the phase change characteristics of the fiber membrane.
[0042] In order to prove the chemical properties of BPAN@PEG4 / BNNS-p, infrared characterization was performed. The test results are as follows: Figure 3 As shown by Figure 3 It can be seen that no new peaks appear in the infrared spectrum, indicating that no new substances are produced and the material has good compatibility. After ultrasonic dip coating and cold pressing of h-BNNS dispersion, the characteristic peaks of h-BNNS in the composite film are more obvious and the peak intensity increases. In addition, the BN stretching vibration and bending vibration peaks are red-shifted, which is attributed to the hydrogen bonding between h-BNNS and PEG and PAN.
[0043] In order to prove the phase change characteristics of BPAN@PEG4 / BNNS-p, cyclic differential scanning calorimetry (DSC) test was carried out. The test results are shown in Figure 4 As shown. Figure 4 It can be seen that after 200 heating / cooling cycles, the intensity and position of the endothermic and exothermic peaks in the DSC curve did not change significantly, confirming the good phase transition reliability and stability of the composite film. The BPAN@PEG / BNNS-p film has a relatively high melting enthalpy of 113.05 J / g, which only loses 0.6% after 200 cycles, and the change in phase transition temperature is negligible.
[0044] In order to prove the thermal conductivity of BPAN@PEG4 / BNNS-p, it was tested by Hot-Disk. The test results are shown in Figure 5 As shown. Figure 5It can be seen that when 4 wt% h-BNNS is incorporated into the sheath solution, the BPAN@PEG film shows an out-of-plane thermal conductivity of 0.048 W / (m·K) and an in-plane thermal conductivity of 1.470 W / (m·K). The thermal conductivity of the composite film is further enhanced by introducing the h-BNNS layer again through ultrasonic dip coating. At this time, the out-of-plane thermal conductivity and in-plane thermal conductivity are 0.107 W / (m·K) and 1.868 W / (m·K), respectively. Cold pressing densifies the composite film, which is beneficial to the improvement of the thermal conductivity of the composite film. BPAN@PEG4 / BNNS-p has an out-of-plane thermal conductivity of 0.210 W / (m·K) and an in-plane thermal conductivity of 2.450 W / (m·K), which are 425% and 168% higher than those of PAN@PEG, respectively. The effective increase in thermal conductivity is mainly attributed to the fact that ultrasonic dipping for an appropriate length of time disperses more thermal conductive fillers more evenly on the coaxial fibers, and then cold pressing strengthens the construction of the overlapping continuous h-BNNS thermal conductive network. The increase in thermal conductivity is conducive to accelerating the phase change thermal response rate of the composite film and promoting its efficiency in the field of thermal management.
[0045] In order to verify the shape stability of BPAN@PEG4 / BNNS-p, the composite film was placed at 80 o C in the oven, the test results are as follows Figure 6 As shown by Figure 6 It can be seen that pure PEG has completely melted after only 15 min, but the mass loss of BPAN@PEG / BNNS-p is only 0.3% after 5 h. This shows that the composite film has excellent shape stability, which is very important for its application in the field of thermal management.
[0046] Example 2 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40 °C for 4 h. 4 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring it at 60 °C for 4 h as the core spinning precursor solution.
[0047] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. oC. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as BPAN@PEG4.
[0048] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on BPAN@PEG4 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The BPAN@PEG4 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 30 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure.
[0049] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 113.99 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.230 W / (m·K) and 0.190 W / (m·K), respectively.
[0050] Example 3 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40 °C for 4 h. 4 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring it at 60 °C for 4 h as the core spinning precursor solution.
[0051] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as BPAN@PEG4.
[0052] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on BPAN@PEG4 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The BPAN@PEG4 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 70 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure.
[0053] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 112.19 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.090 W / (m·K) and 0.150 W / (m·K), respectively.
[0054] Example 4 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h, and 0 wt% h-BNNS was added as the sheath spinning precursor solution; PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring at 60°C for 4 h as the core spinning precursor solution.
[0055] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.24 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as PAN@PEG1.
[0056] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on PAN@PEG1 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The PAN@PEG1 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a high latent heat and high thermal conductivity core-sheath structure phase change fiber.
[0057] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 71.38 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.300 W / (m·K) and 0.180 W / (m·K), respectively.
[0058] Example 5 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h, and 0 wt% h-BNNS was added as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring at 60°C for 4 h as the core spinning precursor solution.
[0059] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.36 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as PAN@PEG2.
[0060] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on PAN@PEG2 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The PAN@PEG2 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a high latent heat and high thermal conductivity core-sheath structure phase change fiber.
[0061] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 82.03 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.220 W / (m·K) and 0.170 W / (m·K), respectively.
[0062] Example 6 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h, and 0 wt% h-BNNS was added as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring at 60°C for 4 h as the core spinning precursor solution.
[0063] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.48 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as PAN@PEG3.
[0064] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on PAN@PEG3 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The prepared PAN@PEG3 phase change fiber membrane was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a high latent heat and high thermal conductivity core-sheath structure phase change fiber.
[0065] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 110.84 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.190 W / (m·K) and 0.171 W / (m·K), respectively.
[0066] Example 7 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h, and 0 wt% h-BNNS was added as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring at 60°C for 4 h as the core spinning precursor solution.
[0067] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as PAN@PEG4.
[0068] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on PAN@PEG4 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The prepared PAN@PEG4 phase change fiber membrane was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a high latent heat and high thermal conductivity core-sheath structure phase change fiber.
[0069] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 112.29 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.090 W / (m·K) and 0.157 W / (m·K), respectively.
[0070] Example 8 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h, and 0 wt% h-BNNS was added as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring at 60°C for 4 h as the core spinning precursor solution.
[0071] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.72 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as PAN@PEG5.
[0072] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on PAN@PEG5 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The PAN@PEG5 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a high latent heat and high thermal conductivity core-sheath structure phase change fiber.
[0073] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 114.29 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.170 W / (m·K) and 0.161 W / (m·K), respectively.
[0074] In order to observe the microstructure of PAN@PEG at different core solution flow rates, SEM and TEM tests were performed on PAN@PAN1, PAN@PAN2, PAN@PAN3, PAN@PAN4 and PAN@PAN5, respectively. The test results are shown in Figure 7 As shown. Figure 7 It can be seen that all coaxial fibers are cylindrical straight fibers, PEG is completely wrapped by the outer layer of PAN, forming an ideal core-sheath structure, and the content of PEG in the fiber increases with the increase of the core layer flow rate. However, when the core layer feed rate is 0.72 mL / h, the PAN@PEG5 fiber membrane exhibits a more serious "beaded" morphology.
[0075] Example 9 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h. 1 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring it at 60°C for 4 h as the core spinning precursor solution.
[0076] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. oC. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as BPAN@PEG1.
[0077] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on BPAN@PEG1 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The BPAN@PEG1 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure.
[0078] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 113.16 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.250 W / (m·K) and 0.191 W / (m·K), respectively.
[0079] Example 10 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40 °C for 4 h. 2 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring it at 60 °C for 4 h as the core spinning precursor solution.
[0080] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as BPAN@PEG2.
[0081] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on BPAN@PEG2 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The BPAN@PEG2 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure.
[0082] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 113.51 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.100 W / (m·K) and 0.178 W / (m·K), respectively.
[0083] Embodiment 11 S1: PAN powder was dissolved in DMF at a concentration of 12% (w / v) by heating it in a water bath at 40°C for 4 h. 3 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h to prepare the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 60% (w / v) by stirring it at 60°C for 4 h to prepare the core spinning precursor solution.
[0084] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 16-21G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 15 cm, the roller speed was 120 rpm, the applied voltage was 25 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 h, a core-sheath phase change fiber membrane was obtained, which was labeled as BPAN@PEG3.
[0085] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on BPAN@PEG3 by combining ultrasonic dip coating and cold pressing. h-BNNS was dispersed in an ethanol solvent at a concentration of 1 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The BPAN@PEG3 phase change fiber membrane prepared above was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent, to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 15 MPa for 30 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure.
[0086] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 113.62 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 2.090 W / (m·K) and 0.176 W / (m·K), respectively.
[0087] In order to observe the microstructure of BPAN@PEG with different h-BNNS additions in the sheath layer, SEM and TEM tests were performed on BPAN@PAN1, BPAN@PAN2, BPAN@PAN3 and BPAN@PAN4, respectively. Figure 8 As shown by Figure 8 It can be seen that in order to improve the thermal conductivity of the fiber membrane, h-BNNS was introduced into the sheath solution as a thermal conductive filler, and the BPAN@PEG membrane was prepared by coaxial spinning. Unlike the smooth surface of PAN@PEG fiber, the fiber surface after adding h-BNNS was slightly rough. As the content of h-BNNS increased from 1 wt% to 4 wt%, the average diameter of the fiber decreased slightly. However, the BPAN@PEG composite fiber still maintained a good porous fiber structure and a clear core-sheath boundary. The loading of h-BNNS in the fiber can be clearly observed by TEM.
[0088] Example 12 S1: PAN powder was dissolved in DMF at a concentration of 10% (w / v) by heating it in a water bath at 40°C for 4 h. 4 wt% h-BNNS was added to PAN / DMF and ultrasonically treated for 2 h. The mixture was then stirred at room temperature for 12 h as the sheath spinning precursor solution. PEG with a molecular weight of 6000 was dissolved in DMF at a concentration of 70% (w / v) by stirring it at 60°C for 4 h as the core spinning precursor solution.
[0089] S2: The obtained spinning precursor solution was stretched into filaments under high pressure by coaxial electrospinning to make core-sheath phase change fibers. A 17G-22G stainless steel coaxial needle was used, the distance between the needle tip and the collecting roller was 17 cm, the roller speed was 120 rpm, the applied voltage was 20 kV, and the relative humidity and temperature were controlled at (40±5)% and (30±3) respectively. o C. The pumping flow rate of the sheath solution was 1.20 mL / h, and the feeding rate of the core solution was 0.60 mL / h. After spinning for 6 hours, a core-sheath phase change fiber membrane was obtained.
[0090] S3: A phase change fiber membrane with a composite core-sheath structure was constructed on the above fiber membrane by combining ultrasonic dip coating and cold pressing treatment. h-BNNS was dispersed in an ethanol solvent at a concentration of 1.5 mg / mL. After 2 h of water bath ultrasound and 12 h of mechanical stirring, a uniformly dispersed h-BNNS dispersion was obtained. The prepared phase change fiber membrane was immersed in the h-BNNS dispersion, ultrasonically treated for 50 min, and then placed at room temperature for vacuum drying for 24 h to remove excess organic solvent to obtain a fiber membrane covered with an h-BNNS thermal conductive layer. The fiber membrane was cold pressed at 10 MPa for 20 min at room temperature to obtain a phase change fiber membrane with a composite core-sheath structure.
[0091] The phase change fiber membrane with a composite core-sheath structure prepared in this embodiment achieves a balance between high phase change latent heat, high thermal conductivity and stability. Its melting enthalpy is 89.15 J / g, and its in-plane thermal conductivity and out-of-plane thermal conductivity are 1.230 W / (m·K) and 0.100 W / (m·K), respectively.
[0092] Therefore, the present invention adopts the above-mentioned phase change fiber membrane with a composite core-sheath structure based on coaxial electrospinning and its preparation method, encapsulates PEG as the core layer in the BNNS / PAN sheath layer, and then uses ultrasonic dip-coating of h-BNNS to further increase the thermal conductive layer, and then strengthens the construction of the interconnected thermal conductive network through cold pressing treatment to obtain a high latent heat and high thermal conductivity composite phase change fiber membrane, which provides technical support for the application of phase change materials in electronic devices and wearable devices.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a phase change fiber membrane with a composite core-sheath structure, characterized in that: The following steps are involved: S1: dissolving polyacrylonitrile in N'N-dimethylformamide, stirring to completely dissolve it, adding hydroxylated boron nitride, and ultrasonically treating to uniformly disperse the hydroxylated boron nitride to obtain a sheath spinning precursor solution; dissolving polyethylene glycol in N'N-dimethylformamide, stirring to melt it, and using it as a core spinning precursor solution; S2: preparing a phase change fiber membrane with a core-sheath structure by a coaxial electrospinning process using the sheath spinning precursor solution and the core spinning precursor solution; S3: placing the phase change fiber membrane with the core-sheath structure in an ethanol dispersion of hydroxylated boron nitride, and performing a cold pressing treatment after ultrasonic dip coating to obtain the phase change fiber membrane with the composite core-sheath structure.
2. The method for preparing a phase change fiber membrane with a composite core-sheath structure according to claim 1, characterized in that: In step S1, the mass / volume concentration of polyacrylonitrile in the sheath spinning precursor solution is 10% to 12%, and the added amount of hydroxylated boron nitride is not more than 5%.
3. The method for preparing a phase change fiber membrane with a composite core-sheath structure according to claim 1, characterized in that: In step S1, the mass / volume concentration of polyethylene glycol in the core layer spinning precursor solution is 50% to 70%.
4. The method for preparing a phase change fiber membrane with a composite core-sheath structure according to claim 1, characterized in that: In step S1, the molecular weight of the polyethylene glycol is 800-6000.
5. The method for preparing a phase change fiber membrane with a composite core-sheath structure according to claim 1, characterized in that: In step S2, during the coaxial electrospinning process, a stainless steel coaxial needle is used, the outer needle of the stainless steel coaxial needle is (15~17)G, and the inner needle is (20~22)G; the pumping flow rate of the sheath spinning precursor solution is 1.2~1.5 mL / h, the pumping flow rate of the core spinning precursor solution is 0.24~0.72mL / h, the applied voltage is 20~25 kV, the spinning distance is 12~17cm, and the roller speed is 100~120 rpm.
6. The method for preparing a phase change fiber membrane with a composite core-sheath structure according to claim 1, characterized in that: In step S3, the concentration of the ethanol dispersion of hydroxylated boron nitride is 1-1.5 mg / mL.
7. The method for preparing a phase change fiber membrane with a composite core-sheath structure according to claim 1, characterized in that: In step S3, the ultrasonic dip coating time is 30 to 70 min, and the cold pressing treatment is performed at room temperature after vacuum drying. The pressure of the cold pressing treatment is 10 to 15 MPa and the time is 20 to 30 min.
8. A phase change fiber membrane with a composite core-sheath structure, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7.
9. The phase change fiber membrane with a composite core-sheath structure according to claim 8, characterized in that: The phase change fiber membrane with the composite core-sheath structure has a melting enthalpy of 71.38-114.29 J / g, an in-plane thermal conductivity of 0.10-0.21 W / (m·K), and an out-of-plane thermal conductivity of 1.23-2.45 W / (m·K).
10. Use of the phase change fiber membrane with a composite core-sheath structure as described in any one of claims 8 to 9 in electronic devices or wearable devices.
Citation Information
Patent Citations
Method for preparing heat-conducting insulating film based on hexagonal boron nitride
CN114481355A
Phase-change temperature-adjusting fiber membrane with skin-core structure for quickly adjusting and controlling temperature of human body and preparation method of phase-change temperature-adjusting fiber membrane
CN114908476A
Method for improving insulation and thermal conductivity of polyetherimide film
CN115260550A
Template transfer print prefabricated filler loaded network high-thermal-conductivity composite film and preparation method thereof
CN118181927A
Method of encapsulating a phase change material
US20230295918A1
Cited By
Conductive temperature-regulating nanofiber core-spun yarn and preparation method thereof
CN120041985A
Preparation method of composite phase-change temperature-regulating organic fiber membrane material with flexible core-shell structure
CN120138888A
Multi-level phase change fabric
CN120588609A